Teacher’s Strategies of English Online Learning during COVID-19 Pandemic in SMA N 8 Purworejo - Selly Shintiani; Semi Sukarni; Edi Sunjayanto Masykuri (Scripta : English Department Journal, 2022)
This research aimed to describe the teaching strategies in online English class and to know the extent of the strategies help the students in learning English during the COVID-19 pandemic at SMA Negeri 8 Purworejo in the academic year of 2020/2021. This type of research was field research with descriptive qualitative research because it described the strategies used by the teachers in SMA Negeri 8 Purworejo when teaching English. Data collection techniques in this study were interview, observation, and documentation. The results of the study shows that the two teachers used five strategies for teaching English during the COVID-19 pandemic namely using methods, approach, using media of online learning, grouping students, and measuring of competence. Both teachers used the same media through WhatsApp group. Secondly, some of the teachers’ strategies in teaching English of online classes could help students, especially practicing speaking and reading by recording videos.